Упростите выражения: а) -2х(1-х)+(2х-3)(х-1)б)4(1+3у)²-24х в)(х+4)(х-4)-(х-3)²...

0 голосов
20 просмотров

Упростите выражения: а) -2х(1-х)+(2х-3)(х-1)
б)4(1+3у)²-24х в)(х+4)(х-4)-(х-3)² г)(а-1)²(2+3а)²
д)(3-b)²(3b+2)²


Алгебра (157 баллов) | 20 просмотров
Дан 1 ответ
0 голосов

а)  -2x +2x^2-2x-3x+3 = 4x^2-7x+3

б) 4(1+6y +9y^2)-24 = 4+24y+36y^2-24 = 36y^2+24y-20

в) x^2 - 16 - x^2+6X-9 = 6x-25

г) 4a^2+12a^3+9a^4-8a-24a^2-18a^3+4+12a+9a^2= 9a^4-6a^3-11a^2+4a+4

д) (9-6b+b^2)(9b^2+12b+4)

 

(2.2k баллов)